Inclusion of mathematics in biological concepts at the senior secondary level in Indian education system - Jaspreet Kaur (Assimilation: Indonesian Journal of Biology Education, 2023)
The students who study biology often develop fear from mathematical concepts and tend to avoid the pages of biology textbook where mathematical details are included. The students often perceive Mathematics and Biology as two separate disciplines of study. One of the main reasons for this perception is that biology textbooks do not include relevant mathematical details in biological concepts. Moreover, biology teachers often have little or no mathematical academic background while mathematics is taught by teachers with least or no interest in biology. This often leads to the lack of understanding among students that both subjects are actually linked to each other. So, the students study them in parallel and there are hardly any cross talks between these two subjects. But, the myth is debunked later when biology students reach the undergraduate and postgraduate level wherein they are expected to apply the mathematical skills to understand the biological concepts. So, if the realization is sparked at an early stage during schooling years that both Mathematics and Biology are related to each other, then the ‘Maths phobia’ among Biology students can be easily overcome. In this article, illustrative examples have been presented with detailed explanation wherein the biology students can appreciate mathematical concepts efficiently in a teaching-learning environment at the senior secondary level.